Exploring the Ethnomathematics Values in the Sikapur Sirih Dance: A Cultural Learning Analysis - Noviyla, Dania; Hariyadi, Bambang; Zurweni, Zurweni; Haryanto, Haryanto (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
Tari Sikapur Sirih is a traditional dance from Jambi that is rich in cultural and aesthetic values. This research aims to explore the ethnomathematical values contained in Tari Sikapur Sirih as part of cultural learning. Tari Sikapur Sirih, which is a cultural heritage of the Jambi community, not only has profound philosophical and spiritual meanings but also contains various mathematical concepts such as patterns, symmetry, and geometry that can be integrated into mathematics learning. Through an ethnomathematical approach, this study analyzes how the dance elements can enrich students' understanding of mathematics contextually while fostering appreciation for local culture. The results of the research indicate that Tari Sikapur Sirih serves as an effective learning medium in connecting cultural values and mathematical concepts, making learning more meaningful and relevant for students while supporting the preservation of traditional culture.